Answer:
The answer should be 752
Step-by-step explanation:
You turn 1/4 into a decimal and you get 0.25
Divide 188 by .25 and you should get that answer
Answer:
x²(9x– 11)(9x + 11)
Step-by-step explanation:
81x⁴ – 121x²
The expression can be factorised as follow:
81x⁴ – 121x²
x² is common to both term. Thus:
81x⁴ – 121x² = x²(81x² – 121)
Recall:
81 = 9²
121 = 11²
Therefore,
x²(81x² – 121) = x²(9²x² – 11²)
= x²[(9x)² – 11²]
Difference of two squares
x²(9x– 11)(9x + 11)
Therefore,
81x⁴ – 121x² = x²(9x– 11)(9x + 11)
12) 12, 8
12 - 8 = 4
12 + 8 = 20
Answer: 4 < x <span>< 20
13) 11, 3
11 - 3 = 8
11 + 3 = 14
Answer: 8 </span>< x <span>< 14
Hope this helps :)</span>
Answer:
(16x + 21) and (16x - 6)
Step-by-step explanation:
f(g(x)) = f(6 + 4x)
Applying the f(x) function on (6 + 4x) gives
4(6 + 4x) - 3
Which equals 16x + 24 - 3
= 16x + 21
g(f(x)) = g(4x - 3)
Applying the g(x) function on (4x - 3) gives
6 + 4(4x - 3)
Which equals 6 + 16x - 12
= 16x - 6